2021
DOI: 10.3390/app11062726
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Inventory Management to Prevent Drug Shortages in the Hospital Supply Chain

Abstract: Drug shortage is always a critical issue of inventory management in healthcare systems since it potentially invokes several negative impacts. In supply chain management, optimization goes hand-in-hand with inventory control to address several issues of the supply, management, and use of drugs. However, it is difficult to determine a shortage situation in a hospital due to multiple unpredictable reasons, such as manufacturing problems, supply and demand issues, and raw material problems. To avoid the shortage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 30 publications
1
16
0
2
Order By: Relevance
“…The unplanned downtime affects the lead time and the waiting time for the customer is increased. Thus, impacts the supply chain efficiency [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The unplanned downtime affects the lead time and the waiting time for the customer is increased. Thus, impacts the supply chain efficiency [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [17] trained an RL agent for a retailer to make appropriate ordering and pricing decisions in a competitive environment. Finally, researchers [18] proposed a deep reinforcement learning model that automatically replenishes the drug prescription inventory to prevent drug shortages in a hospital supply chain. As shown in Figure 1, the intelligent agent will take action according to the current state, obtain a reward from the environment by taking this action, and then decide the most suitable action based on the feedback.…”
Section: Reinforcement Learning (Rl)mentioning
confidence: 99%
“…The research results indicated that random forest and XGBoot were better than other methods. As simulation optimization has been applied in many studies with good results [ 1 , 3 , 21 , 22 , 23 , 24 , 25 ], this study used the simulation optimization method as the main research method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Drug inventory management is an important part of hospital management [ 1 , 2 , 3 , 4 , 5 ]. Drug costs account for 20–25% of hospital management costs.…”
Section: Introductionmentioning
confidence: 99%